A Comprehensive review on 5G-based Smart Healthcare Network Security: Taxonomy, Issues, Solutions and Future research directions - Ahad Abdul; Ali Zahra; Mateen Abdul; Mohammad Tahir; Hannan Abdul; de Garcia Nuno M.; Pires Ivan Miguel (Elsevier B.V., 2025)
Healthcare is experiencing a fast change from a hospital-centric and specialist-focused model to one that is dispersed and patient-centric. Numerous technological advancements are driving this fast evolution of the healthcare sector. Communication technologies, among others, have permitted the delivery of customized and distant healthcare services. The present 4G networks and other wireless communication technologies are being utilized by the healthcare industry to create smart healthcare applications. These technologies are continuously evolving to meet the expectations and requirements of future smart healthcare applications. At the moment, current communication technologies are incapable of meeting the dynamic and complex demands of smart healthcare applications. Thus, the future 5G and beyond 5G networks are expected to support smart healthcare applications such as remote surgery, tactile internet and Brain-computer Interfaces. Future smart healthcare networks will combine IoT and advanced wireless communication technologies that will address current limitations related to coverage, network performance and security issues. This paper presents 5G-based smart healthcare architecture, key enabling technologies and a deep examination of the threats and solutions for maintaining the security and privacy of 5G-based smart healthcare networks